HUBUNGAN TINGKAT PENDIDIKAN DAN SIKAP BIDAN TENTANG PRINSIP KEWASPADAAN UNIVERSAL DENGAN PELAKSANAAN PERTOLONGAN PERSALINAN Di PUSKESMAS RAWATAN Di KOTA PADANG TAHUN 2011 - Selly Septina; Djusar Sulin; Zulkarnaen Agus (Lembaga Penelitian Universitas YARSI, 2015)
Background and objectives Maternal Mortality Rate is one of health indicators as well as of fulfillment of women’s reproductive rights and quality of health services in general. One of the most effective way to reduce is the improvement of the delivery assistance. This study was aimed to learn the level of knowledge and attitude of midviwes about the principles of universal precautions in the implementation ofdeliveryassistance.Materials and Methods Cross sectional analytic approach was applied . Seven health care centers were selected. Manuscript annotation and approval and questionnaires were used for data collection. Subjects were 65 midviwes who helped the delivery of the particular health centers that met the inclusion criteria. Results Majority of midwives involved in this study were between 30-39 years of age with the highest education level was ? diploma D3 (83.1%) and average of 0-9 years of employment (33.8%). In terms of knowledge and attitude, 55.4% and 53.89% subjects showed good knowledge and positive attitude respectively, but a total of 70.7% subjects both possessed good knowledge and positive attitude. Significant correlation was observed between knowledge and professional practice (p value 0.005, p less than 0.05).In whom midwives with higher education performed 7.4 times better attitude. Training also showed significant correlation (p value 0.024) in which the trained midwives on normal delivery care performed 124.3 times better. Conclusion Significant correlation was observed between midwives’ knowledge and professional practice and the principles of universal precautions implementation. There was no significant correlation between attitude and their delivery care and the implementation of principles of universal precautions. Significant correlation was clear between midwives’s education and attitudes, in whom midwives with higher education showed 7.4 times better attitude than those with just adequate education. The trained midwives on normal delivery care performed 124.3 times better than their non-trained counterparts.